Teaching microprocessor course: Challenges and initiatives - Husain, H.; Samad, S. A.; Hussain, A. (2010 2nd International Congress on Engineering Education, 2010)
Identifying the correct approach to teaching microprocessors concepts to Malaysian students is important so as to let them see how the concepts can be applied in practice. This course basically teaches the students on how to design microprocessor-based systems. The students have to understand in detail about the architecture of the microprocessor and learn how to write comprehensive assembly language programs. Teaching and learning the theory of programming is a challenging task since it involves the abstract notions and logical thinking. In addition, they have to have the detailed knowledge on the hardware aspect of the processor. Unfortunately, most of these students adopt a surface approach and tend to accept information passively. They also tend to concentrate only on what will be asked in the examinations and prefer to memorize facts rather than reflecting on the purpose and analyzing the information. They need to adopt a deep approach to learning and interact with the content critically in order to integrate both the hardware and software aspects in their design. This paper discusses the integrated, practical, and student-centered approach for teaching this important subject in the Department of Electrical, Electronics and System Engineering, Universiti Kebangsaan Malaysia (UKM). Although the results shown are favorable, continuous effort is needed to ensure students' comprehension on the concept is well established and sustainable.